Katar of Hindustan: the dagger of tiger hunters (composition, structure and properties) - Kamil S. Haydakov; Dr. Dmitry A. Sukhanov (Историческое оружиеведение)
The weapon complex of Hindustan is represented by one of the most authentic types of H-handled push daggers: “katars” or, as they are called in India, “jamdhars”. Katars are a vivid demonstration of ethnic bladed weapons, which were originally used for hunting large predators and later, under the Mughal dynasties, were used as an integral part of the ruling elite’s traditional costume. Basing on chemical and microstructural analysis, the article describes presumed methods of production of ten Indian katar blades dating from the 16th to 19th centuries.